2019
DOI: 10.3390/antiox9010037
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Inhibits Dopaminergic Neuronal Death of Parkinson’s Disease through Activating Mitophagy

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease, which is associated with mitochondrial dysfunction and abnormal protein accumulation. No treatment can stop or slow PD. Autophagy inhibits neuronal death by removing damaged mitochondria and abnormal protein aggregations. Celastrol is a triterpene with antioxidant and anti-inflammatory effects. Up until now, no reports have shown that celastrol improves PD motor symptoms. In this study, we used PD cell and mouse models to evaluate the therapeutic efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Mitophagy is the selective autophagic degradation of mitochondria; Lin et al (2020) observed that MPP + or MPTP-induced dopaminergic neuronal death, mitochondrial membrane polarization, ATP diminishing which was associated with mitophagy inhibition in SH-SY5Y cells [ 13 ]. For instance, PINK1 ( PARK2 ) and PARKIN ( PARK6 ) regulate mitochondrial function and remove damaged mitochondria by activating mitophagy [ 48 , 49 ].…”
Section: Pathogenesis and Symptoms Of Pdmentioning
confidence: 99%
See 4 more Smart Citations
“…Mitophagy is the selective autophagic degradation of mitochondria; Lin et al (2020) observed that MPP + or MPTP-induced dopaminergic neuronal death, mitochondrial membrane polarization, ATP diminishing which was associated with mitophagy inhibition in SH-SY5Y cells [ 13 ]. For instance, PINK1 ( PARK2 ) and PARKIN ( PARK6 ) regulate mitochondrial function and remove damaged mitochondria by activating mitophagy [ 48 , 49 ].…”
Section: Pathogenesis and Symptoms Of Pdmentioning
confidence: 99%
“…The impairment of the autophagy-lysosome system is progressively observed as a key pathogenic mechanism in PD [ 62 ]. According to Lin et al (2020), the mechanism of celastrol against dopaminergic neuronal death was via increasing autophagosome formation and removing dysfunctional mitochondria by autophagy [ 13 ]. It suggests that autophagy activation is one of the important targets in PD treatment.…”
Section: Pathogenesis and Symptoms Of Pdmentioning
confidence: 99%
See 3 more Smart Citations